Smooth multibidding mechanisms - David Pérez-Castrillo; Nicolas Quérou (Center for Economic Studies and ifo Institute (CESifo), 2011)
We propose a smooth multibidding mechanism for environments where a group of agents have to choose one out of several projects. Our proposal is related to the multibidding mechanism (Pérez-Castrillo and Wettstein, 2002) but it is 'smoother' in the sense that small variations in an agent's bids do not lead to dramatic changes in the probability of selecting a project. This mechanism is shown to possess several interesting properties. First, the equilibrium outcome is unique. Second, it ensures an equal sharing of the surplus that it induces. Finally, it enables reaching an outcome as close to efficiency as is desired.
Keywords: D78; D72; 330; mechanism design; NIMBY; Projektbewertung; Standortwahl; Auktionstheorie; Mechanism Design; Shapley-Wert; Theorie